Ensino de língua espanhola para idosos: mapeamento de pesquisas realizadas no Brasil - Bianchi, Leticia Silva (Universidade Federal de São Carlos, 2021)
This investigation was characterized as an exploratory study, which seeks to map previous research on Spanish language teaching and learning contexts for the elderly people in Brazil, seeking to identify them, characterize them and understand their specificities. We assume that the teaching of foreign languages to the third Age has very unique characteristics, as it is a context in which learning needs are different from the contexts for which, in general, the curriculum and teaching materials of regular schools and of languages are thought (mainly work and tourism). One of our hypotheses was that the main motivation of the elderly people to learn the Spanish language, at this stage of life, is related to issues of hispanic ancestry. Furthermore, based on our theoretical and empirical framework, we infer that the own capabilities and intellectual and cognitive abilities of older people differ from those of young people and adults. In this sense, our second hypothesis was that Spanish teachers for the elderly need to constantly adapt the available materials and make use of strategies to "compensate" them for possible identified difficulties. Therefore, the general objectives of the research were to carry out a bibliographic review of research carried out in Brazil that investigated the teaching of Spanish language for the elderly people and to identify the characterization of the contexts regarding the learning needs presented by senior students, the didactic strategies and approaches mobilized by the responsible teachers, seeking to identify the specificities that permeate the teaching and learning process of the elderly in this context and that determine/generate input for the definition and construction of possible teaching approaches. As a result, our bibliographical research found a shortage of works focusing on the Spanish language, which highlights a gap in research and confirms the need for this type of study to understand, in a targeted way, the specific aspects of teaching and learning Spanish to the elderly people. In addition, it was possible to understand universal and specific aspects of the needs and the learning processes of older adults, demonstrating the indispensability of producing new studies in the area, aiming at the advancement and development of methodologies, materials and educational policies for senior people.
Enseñanza de español para personas mayores: investigaciones desarrolladas en Brasil
Keywords: ensino de espanhol; idosos; Terceira idade; teaching spanish; seniors; third age; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA